Proton-conducting ceramics for water electrolysis and hydrogen production at elevated pressure - Herradon, C.; Le, L.; Meisel, C.; Huang, J.; Chmura, C.; Kim, Y.D.; Cadigan, C.; O’Hayre, R.; Sullivan, N.P. (Frontiers in Energy Research, 2022)
Pressurized operation is advantageous for many electrolysis and electrosynthesis technologies. The effects of pressure have been studied extensively in conventional oxygen-ion conducting solid-oxide electrochemical cells. In constrast, very few studies have examined pressurized operation in proton-conducting electroceramics. Protonic ceramics offer high proton conductivity at intermediate temperatures (∼400–600°C) that are well-matched to many important thermochemical synthesis processes. Pressurized operation can bring significant additional benefits and/or provide access to synthetic pathways otherwise unavailable or thermodynamically disfavorable under ambient conditions and in higher- or lower-temperature electrochemical devices. Here we examine pressurized steam electrolysis in protonic-ceramic unit-cell stacks based on a BaCe0.4Zr0.4Y0.1Yb0.1O3−δ (BCZYYb4411) electrolyte, a Ni–BZCYYb4411 composite negatrode (fuel electrode) and a BaCo0.4Fe0.4Zr0.1Y0.1O3−δ (BCFZY) positrode (air-steam electrode). The cells are packaged within unit-cell stacks, including metallic interconnects, current collectors, sealing glasses and gaskets sealed by mechanical compression. The assembly is packaged within a stainless steel vessel for performance characterization at elevated pressure. Protonic-ceramic electrolyzer performance is analyzed at 550°C and pressures up to 12 bara. Increasing the operating pressure from 2.1 to 12.6 bara enables a 40% overall decrease in the over-potential required to drive electrolysis at 500 mA cm−2, with a 33% decrease in the cell ohmic resistance and a 60% decrease in the cell polarization resistance. Faradaic efficiency is also found to increase with operating pressure. These performance improvements are attributed to faster electrode kinetics, improved gas transport, and beneficial changes to the defect equilibria in the protonic-ceramic electrolyte, which more than compensate for the slight increase in Nernst potential brought by pressurized operation. Electrochemical impedance spectroscopy (EIS) coupled with distribution of relaxation time (DRT) analysis provides greater insight into the fundamental processes altered by pressurized operation.